Skin and eye protection against ultraviolet C from ultraviolet germicidal irradiation devices during the COVID‐19 pandemic - Lyons, Alexis B. (Int J Dermatol, 2020)
With the COVID‐19 pandemic depleting personal protective equipment worldwide, various methods including ultraviolet C (UVC) germicidal irradiation (UVGI) have been implemented to decontaminate N95 filtering facepiece respirators. These devices pose a risk for UVC exposure to the operator with reported adverse effects generally limited to the eyes and skin. Our hospitals are currently using UVC devices for N95 decontamination with a few reported cases of face and neck erythema from exposure. Because sunscreens are designed and tested for UVA and UVB protection only, their effects on blocking UVC are largely unknown. Therefore, our objective was to determine if various sunscreens, UV goggles, and surgical mask face shields minimize UVC exposure from UVGI devices. Our study clearly demonstrated that healthcare workers responsible for the disinfection of PPE using UVGI devices should always at least utilize clear face shields or UV goggles and sunscreen to protect against side effects of UVC exposure.